2017
DOI: 10.1021/acs.energyfuels.7b02517
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bacillus spp. in Pilot Test of Microbial Huff and Puff to Improve Heavy Oil Recovery

Abstract: Microbial metabolic products, such as biosurfactants, bioemulsifiers, acids, solvents, and biogases, are useful for reducing the viscosity of heavy oils and enhancing oil recovery. Two heavy oil viscosity-reducing microorganisms, namely, SH-2 and SH-3, were selected from produced water which were collected from high-temperature reservoirs by enrichment culture technique. The screened bacteria produce biosurfactants and biogases that can biodegrade heavy crude oil components. The screened bacteria combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…E4 had greater viscosity reduction efficiency (66.33%) than E2 (53.87%). Previous studies have shown that some bacterial strains (e.g., Bacillus subtilis, B. licheniformis, and Geobacillus stearothermophilus) reduce heavy oil viscosity by 15.47-40.06% under aerobic and aerobic conditions [26,27]. Compared with these bacteria, the fungal enzyme preparations exhibited markedly higher abilities to decrease heavy oil viscosity in the current study.…”
Section: Viscosity Reduction Of Heavy Oilmentioning
confidence: 48%
“…E4 had greater viscosity reduction efficiency (66.33%) than E2 (53.87%). Previous studies have shown that some bacterial strains (e.g., Bacillus subtilis, B. licheniformis, and Geobacillus stearothermophilus) reduce heavy oil viscosity by 15.47-40.06% under aerobic and aerobic conditions [26,27]. Compared with these bacteria, the fungal enzyme preparations exhibited markedly higher abilities to decrease heavy oil viscosity in the current study.…”
Section: Viscosity Reduction Of Heavy Oilmentioning
confidence: 48%
“…The two fungal enzyme preparations with a nal concentration of 4% (w/v) were able to reduce the viscosity of heavy oil from 29,700 to 13,700 (E2) and 10,000 (E4) mPa s. This result showed that E4 had greater viscosity reduction e ciency (66.33%) than E2 (53.87%). Other studies have shown that some bacterial strains (e.g., Bacillus subtilis, B. licheniformis, and Geobacillus stearothermophilus) reduce heavy oil viscosity by 15.47-40.06% under aerobic and aerobic conditions [26,27]. Compared to these bacteria, the fungal enzyme preparations tested in the current study exhibited markedly higher abilities to reduce heavy oil viscosity.…”
Section: Viscosity Reduction Of Heavy Oilmentioning
confidence: 49%
“…The degradation e ciency of different heavy oil fractions by bacterial consortia was reported to be 10.57-23.68% for alkanes, 6.03-20.62% for aromatics, and 3.63-16.90% for resins and asphaltenes [10,26,27]. By comparison, the fungal enzyme preparations from our Aspergillus cultures had higher abilities to degrade saturates, while the aromatic and resin fractions of heavy oil were relatively increased after enzymatic degradation.…”
Section: Effect Of Enzyme Concentration On Heavy Oil Degradationmentioning
confidence: 78%
“…The degradation efficiency of different heavy oil fractions by bacterial consortia was reported to be 10.57%–23.68% for alkanes, 6.03%–20.62% for aromatics, and 3.63%–16.90% for resins and asphaltenes 11,29,30 . By comparison, the crude enzyme extracts from our Aspergillus cultures had higher abilities to degrade saturates (decreased by 16.27%–27.61%), while the aromatic and resin fractions of heavy oil were relatively increased (decreased by 30.85%–64.89% and 2.45%–40.49%, respectively) after treatment.…”
Section: Resultsmentioning
confidence: 71%